PENGARUH LEARNING ORGANIZATION DAN SELF EFFICACY TERHADAP KINERJA PEGAWAI DIMEDIASI KNOWLEDGE SHARING PADA DINAS TENAGA KERJA KOTA PASURUAN - Heny Diane Yusnita; Sodik, Sodik; T. Kuncoro (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This study aims to obtain empirical evidence of the ability of learning organization and self-efficacy in encouraging employee performance improvement, either directly or through knowledge sharing mediation.This type of research is quantitative with the SEM-SmartPLS method. Data were obtained through questionnaires which were distributed to 37 employees of the Pasuruan City Manpower Office.Empirical evidence shows that both learning organization and self-efficacy are both able to strongly encourage increased knowledge sharing, but on employee performance, learning organization has a weak effect, and self-efficacy can strongly improve employee performance. The role of knowledge sharing as a mediation is very strong, both in mediating the influence of learning organization on employee performance and on the effect of self-efficacy on employee performance. This finding is supported by the description of the four variables, all of which received high responses, including observing and thinking in a system, full of pressure, telling colleagues, and according to targets